Community Capacity in Dealing with Disasters in Banyumanik Sub-District, Semarang City: Kapasiti Komuniti dalam Menangani Bencana di Sub-Daerah Banyumanik Kota Semarang - Tjahjono, Heri; Juhadi, .; Santoso, Apik Budi; Suharyanto, . (GEOGRAFI, 2021)
This study aims (1) to determine the level of community capacity in dealing with landslides in the Banyumanik Sub-District, (2) to analyse various determining factors on community capacity. This research took a population of people living in the Banyumanik Sub-District, Semarang City. Sampling was done applying purposive sampling based on specific considerations or objectives, namely choosing people living around landslides-affected or prone areas. The community capacity assessment in this study developed the capacity indicator framework of the Hyogo Framework for Actions (HFA) consisting of five variables, namely (a) disaster management rules and institutions, (b) early warning and disaster risk assessment, (c) disaster education, (d) reduction of primary risk factors, and (e) development of preparedness in all lines. Data collection was executed by utilizing questionnaires and interviews. It was then analysed by scoring. The results demonstrate that the community capacity in dealing with landslides, in general, is as follows: 38.78% of respondents have low criteria, 36.73% are categorized in the medium criteria, and 24.49% of people possess high category in terms of community capacity.